2002
DOI: 10.1002/app.10417
|View full text |Cite
|
Sign up to set email alerts
|

Moisture‐sorption characteristics of starch/low‐density polyethylene films

Abstract: Moisture-sorption characteristics of starch/low-density polyethylene (LDPE) blends were carried out at 27°C for water activity (a w ) from 0.1 to 0.9. The sorption data were used to fit six different sorption isotherm models proposed in the literature. The model constants were determined by linear fitting of the sorption equations. The ranges of applicability of water activity for the isotherm models reported in the article lies between 0.1 and 0.4 (monomolecular layer) for the BET model and between 0.3 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The experimental sorption data applied to the BET model for various starch contents of the PVA/starch films, as shown in Figure 3(A), were found to fit well for a w ϭ 0.1-0.4. Chirife and Iglesias 11 and Raj et al 3 demonstrated that the BET equation was good for the aforementioned range of a w . The BET constants were determined from a linear fitting of the BET equation, 3 and the corresponding values are given in Table I.…”
Section: Sorption Model Analysismentioning
confidence: 97%
See 4 more Smart Citations
“…The experimental sorption data applied to the BET model for various starch contents of the PVA/starch films, as shown in Figure 3(A), were found to fit well for a w ϭ 0.1-0.4. Chirife and Iglesias 11 and Raj et al 3 demonstrated that the BET equation was good for the aforementioned range of a w . The BET constants were determined from a linear fitting of the BET equation, 3 and the corresponding values are given in Table I.…”
Section: Sorption Model Analysismentioning
confidence: 97%
“…Chirife and Iglesias 11 and Raj et al 3 demonstrated that the BET equation was good for the aforementioned range of a w . The BET constants were determined from a linear fitting of the BET equation, 3 and the corresponding values are given in Table I. The values of M m varied from 3.08 to 7.88, indicating that different PVA/starch blends had different capacities for moisture sorption and also for the availability of free water.…”
Section: Sorption Model Analysismentioning
confidence: 97%
See 3 more Smart Citations